Different genetic requirements for repair of replication-born double-strand breaks by sister-chromatid recombination and break-induced replication - Cortés-Ledesma, Felipe (Oxford University Press, 2007)
Homologous recombination (HR) is the major mechanism used to repair double-strand breaks (DSBs) that result from replication, but a study of repair of DSBs specifically induced during S-phase is lacking. Using an inverted-repeat assay in which a DSB is generated by the encountering of the replication fork with nicks, we can physically detect repair by sister-chromatid recombination (SCR) and intra-chromatid break-induced replication (IC-BIR). As expected, both events depend on Rad52, but, in contrast to previous data, both require Rad59, suggesting a prominent role of Rad59 in repair of replication-born DSBs. In the absence of Rad51, SCR is severely affected while IC-BIR increases, a phenotype that is also observed in the absence of Rad54 but not of its paralog Rdh54/Tid1. These data are consistent with SCR occurring by Rad51-dependent mechanisms assisted by Rad54, and indicate that in the absence of strand exchange-dependent SCR, breaks can be channeled to IC-BIR, which works efficiently in the absence of Rad51. Our study provides molecular evidence for inversions between repeats occurring by BIR followed by single-strand annealing (SSA) in the absence of strand exchange.